2009
DOI: 10.1254/jphs.09081fp
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor–α (TNF-α) Induces Upregulation of RhoA via NF-κB Activation in Cultured Human Bronchial Smooth Muscle Cells

Abstract: Abstract. RhoA plays an important role in Ca 2+ sensitization of bronchial smooth muscle in antigen-induced airway hyperresponsiveness (AHR). Tumor necrosis factor-α (TNF-α), a major proinflammatory cytokine, is capable of inducing AHR, but the mechanisms for this are still unknown. In the present study, the effect of TNF-α on RhoA protein expression was examined in cultured human bronchial smooth muscle cells (hBSMCs). To investigate the role of NF-κB in the TNF-α-induced upregulation of RhoA, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…In our previous study, the increase in the nuclear p65 was observed when cells were stimulated with 10 ng/mL of TNF-α for 30 min, and the increase in nuclear p65 induced by TNF-α was significantly inhibited by BMS-345541 in a concentration-dependent manner in hBSMCs [37]. Furthermore, TNF-α-induced increase in RhoA protein was inhibited by BMS-345541 [37].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the increase in the nuclear p65 was observed when cells were stimulated with 10 ng/mL of TNF-α for 30 min, and the increase in nuclear p65 induced by TNF-α was significantly inhibited by BMS-345541 in a concentration-dependent manner in hBSMCs [37]. Furthermore, TNF-α-induced increase in RhoA protein was inhibited by BMS-345541 [37].…”
Section: Resultsmentioning
confidence: 99%
“…The RhoA mRNA expression in human bronchial smooth muscle can also be induced by cytokines, such as IL-13 and TNF-α, and additionally, STAT6 and NF-κB are important for this up-regulation [34]. TNF-α can also induce the up-regulation of RhoA via NF-κB activation in cultured human bronchial smooth muscle cells [35]. This up-regulation mechanism of RhoA was mediated by GEFF-H1, as the siRNA-induced down-regulation of GEFF-H1 prevented the activation of the Rho pathway [36].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used TNFα concentrations with physiological effects are between 10–100 ng/ml [29], [30], [31]. We used concentration of 50 ng/ml for our studies.…”
Section: Discussionmentioning
confidence: 99%